ЗАМАХШАРИЙ АСАРЛАРИДА САБР ВА ҚАНОАТ ТУШУНЧАЛАРИ ТАЛҚИНИ - Сулаймонова, Н. (SCIENCE and SOCIETY, 2020)
The article analyzes the views of the thinker Mahmoud Zamakhshari, some aphorisms from his didactic work “Atvaku-z-zabab” (“Golden Necklaces”), devoted to the interpretation of such human qualities as patience, endurance are quoted.